Condicionais e implicaturas: uma avaliação das teorias da equivalência de Grice e Jackson - Matheus Martins Silva (2011)
The equivalence theory claims that the truth-conditions of indicative conditional sentences are equivalent to the truth-conditions of the material conditional in classical logic. This theory has many defenders, Paul Grices work being the classical reference and the most influential recent defense is the one presented by Frank Jackson. Our main goal is to evaluate the equivalence theory as formulated by these two authors. Both aim at explaining the equivalence between the material conditional and indicative conditional sentences by means of pragmatic elements inlanguage use: Grice by means of implicatures and conversational maxims, and Jackson through conventional implicatures and robustness. We will argue that those solutions face big difficulties. Grice's proposal is incapable of explaining why apparently the conversational implicatures ofindirectness arent cancelable and Jacksons solution doesnt resist to the fact that assertibility its not measured by degrees. However, we will defend in the conclusion that influential alternatives also face serious problems. For this reason, and considerations of simplicity and explanation power, the pragmatic defenses of the equivalence theory still seem to us to be relevant alternatives, in spite of its shortcomings.